Coriocarcinoma no gestacional primario de ovario. A propósito de un caso y revisión de la literatura - Gonzales-Medina, Carlos (2021)
We present the clinical case of a patient with a diagnosis of primary non-gestational ovarian choriocarcinoma corresponding to a germline malignant neoplasm. Likewise, the updated literature on the subject is reviewed, emphasizing molecular biology, diagnosis, and initial cancer management. It was developed at the Dos de Mayo National Hospital (HNDM) in the Oncology Gynecology Service, Lima, Peru. The present case is recorded due to its limited casuistry in our setting and due to the important value of oncological criteria in the management of adnexal ovarian masses.